ANALYSIS OF DETERMINANT FACTORS FOR WARDAH BEAUTY PRODUCT DEMAND IN SURAKARTA - Athik Hidayati Setyaningsih; Bhimo Rizky Samudro; Untari Eka Setiawati (Journal of Applied Economics in Developing Countries, 2021)
In this modern era, a person is needed to look attractive, especially a woman. To be more confident, they use cosmetics in daily life. That's what makes beauty products in high demand. The increased demand for beauty products has made companies engaged in beauty compete to launch their best products. One of the local beauty products that have high demand in Indonesia is Wardah cosmetics. Some things can make this beauty product so attractive to many people. This study intends to conduct a Factor Analysis of the Demand Determinants of Wardah Beauty Products in Surakarta. The content analysis technique used is multiple linear regression analysis with primary data. The results of the research show that quality and packaging have a significant positive effect on the demand for Wardah beauty products. Keywords: Price; Quality; Packaging; Wardah Beauty Products